PENGARUH CASH RATIO DAN DEBT TO EQUITY RATIO TERHADAP NET PROFIT MARGIN PADA PT. MAYORA INDAH TBK. PERIODE 2016-2019 - Eman Singgih (JUBISMA, 2021)
PT. Mayora Indah Tbk. was established on February 17, 1997. It is a company in the food and beverage sector with its address in West Jakarta, which is located at Jl. Tomang Raya 21-23.This research was conducted to examine the variables CashRatio (CR) and Debtto Equity Ratio (DER) to Net Profit Margin (NPM) at PT. Mayora Indah Tbk. This research is a research conducted from September to November 2021 on the Jakarta Stock Exchange using a quantitative approach. This study uses quantitative data in the form of financial statements from the company PT. Mayora Indah Tbk. which is listed on the Indonesia Stock Exchange and has published its financial statements for 2016–2019. Before analyzing the data using statistics, the dependent variable and independent variables will be calculated by using a ratio scale The population in this study is the financial statements of PT. Mayora Indah Tbk. The sampling technique used is purposive sampling for the 2016-2019 quarter. The results of the study show either partially or simultaneously, that Cash Ratio (CR) and Debtto Equity Ratio (DER) have a positive and significant effect on Net Profit Margin (NPM).For further researchers, it is hoped that they can examine other variables outside of this variable, in order to obtain results that can affect the Net Profit Margin (NPM). Keywords: Effect of Cash Ratio (CR) and Debtto Equity Ratio (DER) on Net Profit Margin (NPM).